A RELATIONSHIP BETWEEN THE HONEYCOMB APPEARANCE ON CT SCAN AND LIFE EXPECTANCY IN PATIENTS WITH SCLERODERMA? A SYSTEMATIC REVIEW - Haekal Mahargias; Febrina Mayasari Gunawan; Mutiara Amalia (The Indonesian Journal of General Medicine, 2026)
Introduction: Systemic sclerosis (SSc) is a complex autoimmune disease frequently complicated by interstitial lung disease (ILD), a leading cause of mortality. The honeycomb appearance on high-resolution computed tomography (HRCT) represents advanced pulmonary fibrosis, but its prognostic significance in SSc-ILD remains debated. This systematic review aims to evaluate the relationship between honeycomb appearance on CT scan and life expectancy in patients with scleroderma. Methods: A systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria: confirmed SSc diagnosis, evaluation of honeycomb pattern on CT, reported survival outcomes, appropriate observational study design, adequate follow-up, and sufficient sample size (>10 patients). Data extraction encompassed study characteristics, CT methodology, honeycomb definition, survival outcomes, and statistical associations. Quality assessment and multivariate analyses were evaluated. Results: Among 198 included studies, sample sizes ranged from 10 to 62,930 patients, with follow-up periods from 12 months to over 20 years. Honeycombing prevalence in SSc-ILD cohorts ranged from 37.2% to 41.9%, with higher frequency in limited cutaneous SSc. Multiple studies demonstrated significant associations between honeycombing and mortality, with hazard ratios ranging from 1.72 (95% CI 1.38-2.14) to 4.64 (95% CI 1.68-12.81). The association persisted after adjusting for age, gender, pulmonary function tests, and scleroderma subtype. Automated quantitative CT methods (CALIPER) showed improved reproducibility compared to visual scoring. Discussion: This review provides robust evidence that honeycomb appearance on CT scan is an independent predictor of reduced life expectancy in SSc-ILD patients. Honeycombing represents irreversible fibrotic damage and consistently outperforms inflammatory features (ground-glass opacities) in prognostic value. Heterogeneity in honeycomb definitions and quantification methods remains a limitation. Conclusion: Honeycomb appearance on HRCT is a critical prognostic marker in SSc-ILD, associated with 2-3 fold increased mortality risk. Standardized CT reporting and incorporation of honeycombing into clinical risk stratification models are recommended. Future research should focus on automated quantitative assessment and validation of honeycombing-specific therapeutic algorithms.